Current-limited voltage control strategies for multiple-input buck converters applied in renewable energy hybrid systems - Xian, Liang (2015)
Current-limited voltage control strategies (CLVCSs) are required by kinds of renewable energy hybrid systems. For small-scaled loads such as portable electronic devices and electric vehicles, multiple-input buck converters (MIBCs) are the preferred candidate, if introducing renewable energy sources to power them. In this paper, three CLVCSs-independence CLVCS, addition CLVCS, and subordination CLVCS-which are applied in the input-capacitor-added (ICA) MIBC topology, are put forward and compared based on the simulation stage. The results show, when designing the CLVCS structure, the consideration of building up a proper connection of the duty cycles, as the subordination CLVCS did, is able to improve the stability and robustness of the controlled output voltage of the ICA MIBC, whereas at the expense of less control accuracy of limiting the output current of the power source.